How many medications do doctors in primary care use? An observational study of the DU90% indicator in primary care in England. Issue 3 (2nd March 2021) - Chiedozie, Chiamaka; Murphy, Mark E; Fahey, Tom; Moriarty, Frank
Abstract : Aim: To apply the drug utilisation 90% (DU90%) indicator (the number of unique drugs which makes up 90% of a doctor's prescribing) to general practitioner (GP) practices prescribing in England to examine time trends, practice-level variation, and relationships with practice characteristics, prescribing costs and low-value prescribing. Study design: Retrospective cohort study. Setting: Primary care in England, using publicly available prescribing data available from the National Health Service (NHS) digital platform for 2013–2017. Participants: All general practices in England (n=7620). Primary and secondary outcome measures: The DU90% was calculated on an annual basis for each practice based on medication British National Formulary codes. Low-value prescribing was defined using NHS 2017 guidance (including lidocaine plasters, liothyronine, omega-3 supplements). Descriptive statistics were generated per year on time trends and practice-level variation in the DU90%. Multilevel linear regression was used to examine the practice characteristics (relating to staff, patients and deprivation of the practice area). Results: Among 7620 practices, mean DU90% ranged from 130.0 to 131.0 across study years, and regarding variation between practices, there was a 1.4-fold difference between the lowest and highest 5% of practices. A range of medications were included in the DU90% of virtually all practices, including atorvastatin, levothyroxine, omeprazole, ramipril, amlodipine, simvastatin and aspirin. A higher volume of prescribing was associated with a lower DU90%, while having more patients, higher proportions of patients who are women or aged ≥45 years, higher number of GPs working in the practice and being in a more deprived area were associated with a higher DU90%. Practices in higher quintiles of DU90% had higher levels of low-priority prescribing and prescribing costs. Conclusion: GP practices typically use 130 different medications in the bulk of their prescribing. Higher DU90% was associated with higher levels of low-priority prescribing and prescribing costs. Increasing use of personal formularies may enhance prescribing quality and reduce costs.